2016
DOI: 10.4158/ep15657.cr
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Association Between Pituitary Tumor Apoplexy and Influenza A

Abstract: Objective: Pituitary adenomas have a population prevalence of less than 0.1%. They can rarely present with serious complications, such as pituitary tumor apoplexy with symptoms of sudden severe headache, vision impairment, nausea, and vomiting. Methods: To date, there has been no proven underlying mechanism for the development of pituitary apoplexy. We report a novel association between pituitary tumor apoplexy and influenza A, indicating an inflammatory pathology underlying influenza infection contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Recently, Frara et al and Kamel et al showed that SARS-CoV-2 may cause pituitary apoplexy in the context of pre-existing macroadenomas (1,6). Previously, Tariq et al reported an association between influenza A infection and pituitary tumour apoplexy (4). Even though a causative link could not be demonstrated, influenza infections have been documented to increase haemorrhagic risk in multiple organs (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Frara et al and Kamel et al showed that SARS-CoV-2 may cause pituitary apoplexy in the context of pre-existing macroadenomas (1,6). Previously, Tariq et al reported an association between influenza A infection and pituitary tumour apoplexy (4). Even though a causative link could not be demonstrated, influenza infections have been documented to increase haemorrhagic risk in multiple organs (4).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Tariq et al. reported an association between influenza A infection and pituitary tumour apoplexy ( 4 ). Even though a causative link could not be demonstrated, influenza infections have been documented to increase haemorrhagic risk in multiple organs ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations